Конструктивно-географічна оцінка стану гідроморфних меліорованих ґрунтів Волинської області - Полянський, Сергій Володимирович; Polianskyi, Serhii V. (Тернопільський національний педагогічний університет імені Володимира Гнатюка, 2014)
У статті розглянуто критерії та особливості формування бальної оцінки меліорованих земель. У результаті конструктивно-географічних досліджень розроблені й обґрунтовані критерії та алгоритм оцінки меліорованих агроландшафтів Волинської області, запропонований математичний апарат для розрахунку параметрів оцінки, проведені основні розрахункові процедури, розраховано значення комплексної конструктивно-географічної оцінки екологічного стану ґрунтів, за ними побудовано синтетичну картосхему. Також проведено кластерний аналіз для верифікації результатів моделювання та оцінки екологічного стану агроландшафтів.

The article reviews the criteria and features of the formation of meliorated soils evaluation. Structural and geographical researches of environmental management, improvement and radical change in the territorial organization of natural and economic systems, changing of the nature by the requirements of the technology to the direction of technologies adaptation to the the structure and function of the nature were made. Structural and geographical analysis of the meliorated soils allows to detect ties of complex natural ingredients and means of industry impact, which determine the agricultural potential of areas . As a result of structural and geographical studies criteria and algorithm of the evaluation of meliorated agrolandscapes of Volyn region were developed and found. The proposed mathematical apparatus of parameter estimation was carried out. Basic calculation procedures were made. Value of the complex structural and geographical assessment of environmental condition of the soil was calculated, according to which synthetic map-scheme was build. Cluster analysis of verification of simulation results and of the ecological state of agrolandscapes assessment was conducted.
Structural and geographical zoning of the condition of meliorated soils of Volyn region.
Keywords: меліорація; критерії; бальна оцінка; м оцінка екологічного стану; melioration; criteria; assessment of the ecological status; evaluation